Equivalence and performance gaps in Swedish school inspection: context and the politics of blame. Issue 1 (2nd January 2016) - Carlbaum, Sara
Abstract : This article analyses and critically discusses how context is relevant when constructing and upholding an equivalent education for all within the neo-liberal educational regime of marketisation and accountability. At the centre of the article is a study of national school inspection reports in four municipalities in Sweden, exploring performance gaps, equality and justice in an educational system, that for decades has emphasised universal welfare, justice and equality. By drawing on the concept of 'the politics of blame', findings show that accountability and blame are constructed in complex ways. Although teachers and schools are blamed for low expectations with little contextual consideration by Swedish Schools Inspectorate, local governments are blamed for not redistributing resources. This can both challenge and strengthen the contemporary regime in governing education.